Accuracy of gamma-glutamyl transpeptidase-to-platelet ratio (GPR), red cell distribution width (RDW), aspartate aminotransferase-to-platelet ratio index (APRI), and the fibrosis-4 index (FIB4) compared with liver biopsy in patients with drug-induced liver injury (DILI). Issue 6 (12th February 2021) - Wan, Minjie; Xu, Hongqin; Li, Dezhao; Wang, Le; Li, Xu
Abstract : Abstract: This study objected to evaluate the accuracy of the gamma-glutamyl transpeptidase-to-platelet ratio (GPR), aspartate aminotransferase-to-platelet ratio index (APRI), red cell distribution width (RDW), and fibrosis-4 index (FIB4) index, compared with liver biopsy (LB), in predicting the severity of inflammation in drug-induced liver injury (DILI) patients. We evaluated patients with DILI who were followed at the First Hospital of Jilin University and underwent LB. Accuracy of each method was analyzed using ROC analysis. Classifications of liver inflammation included G0–4. One hundred fifty six DILI patients were included with LB and complete medical records. 62.8% (98), 39.1% (61), and 16.7% (26) were classified as ≥G2, ≥G3, or G4, respectively. The AUROCs, by degree of inflammation, were: ≥G2: GPR: 0.654, RDW: 0.635, APRI: 0.728, and FIB4: 0.739; ≥G3: GPR: 0.623, RDW: 0.703, APRI: 0.777, and FIB4: 0.781; and G4: GPR: 0.556, RDW: 0.647, APRI: 0.729, and FIB4: 0.714. To predict ≥G2 inflammation, there were no differences between the AUROCs for GPR, RDW, APRI, and FIB4. To predict ≥G3 inflammation, the AUROCs for FIB4 and APRI were higher than that for GPR (0.781 vs 0.623, P < .01; 0.777 vs 0.623, P < .05). As for G4 inflammation, the AUROCs for FIB4 and APRI were also higher than GPR (0.714 vs 0.556, P < .05, 0.729 vs 0.556, P < .05). When the level of inflammation was higher than G2 in patients with DILI, it could be predicted using APRI and FIB4 as non-invasive markers for this condition.